PERSEPSI KALANGAN REMAJA SMA MENGENAI PERAN GENDER DALAM PERSPEKTIF ISLAM - Cindy Olanda Dewi; Ashif Az Zafi (IAIN Purwokerto, 2020)
Bisically, men and women have a same justice, ability, intelligence. In the Al-Quran also explained that in islam there is no difference between men and women, in front of Allah SWT all the same. And now there are only a lot of cases of sexual harassment among teemagers. Whit this problem, sex education is ane way that can be used. The purpose of this research is to find out the perception of senior high school adolescents regarding gender roles in Islam. The type of research is quantitative conducted by random.